Religion, Animals and Reception: Reconsidering the Naḥash - Crane, Jonathan K. ca. 20./21. Jh. (Religions, 2022)
This paper explores the narrative contribution of visual images of nonhuman animals, and of desire in particular, by considering the exemplum of the Biblical nachash, commonly known as a serpent or snake. The Biblical textual depiction of this creature indicates that it is not different in kind from humans but only different by degree. Later artists expand upon these possibilities in creative and provocative ways. By using a visual critical approach, the paper reviews the Garden of Eden story, and then examines an array of images that expand and challenge the text.